Technological roulette for socio-affective development in children from 2 to 3 years old (Ciencias de la Ingeniería y Aplicadas, 2018)
The technological roulette for the socio-affective development of children from two to three years old is a project aimed at the Children's Centers for Good Living (CIBV) of the Eloy Alfaro parish of the Latacunga Canton. The stages of diagnosis of the socio-affective conditions of the CIBV children were followed; In the second stage, the analysis of the bibliographic base was carried out; In the third stage, the technological tool was developed, for this, based on the specification of software requirements, a mobile application (App) was developed that connects with the physical structure of the roulette wheel and serves as command control for the user. . The people who manipulate the tool are the CIBV kindergarten teachers. In general, a usable tool was designed where the direct beneficiaries are children from 2 to 3 years of age. The proposal was implemented in one of the CIBV, verifying the use and behavior of children and teachers through several instruments, which gave the results that: roulette is an effective resource to stimulate the development of the socio-affective capacities of children, it was evident that with the use of the tool the children improved in their concentration, interest in developing different activities and, above all, in their ability to work in groups; Furthermore, it was observed that the interaction of the child with the nursery teacher through the Play-Work method is more efficient for their socio-affective development.
Keywords: Socio-Affective Development; Technological Tool; Ruler; Application